Effects research on theoretical-modelling based suppression of the contact flutter in blisk belt grinding. (June 2020) - Huang, Yun; He, Shui; Xiao, Guijian; Li, Wei; Jiahua, Suolang; Wang, Wenxi
Abstract: Blisk is one of the critical parts of aero-engine whose surface processing quality directly affects the performance of aero-engine. The vibration phenomenon usually happened in the novel open belt grinding, and seriously affects the dimension precision as well as the surface quality of the whole blade profile. In order to figure out that, this paper established a vibration model for the blisk belt grinding. The weak rigidity characteristics of the system were analyzed initially, and the vibratory mechanism was revealed from the view of dynamic analysis. Based on the theoretical model, the stability conditions were proposed by analyzing the influencing of vital factors on processing stability. The experimental validation indicated that the vibration signal waveforms during the process had been successfully reduced by introducing adjustment of grinding parameters. The profile accuracy of the blade contour edge was improved by 9.53 % from the range of −0.0376–0.1145 mm to that of −0.0359–0.1017 mm. After parameter adjustment, the smoothness of the micro-morphology of the blade surface was improved, and the roughness of the blade surface decreased from Ra 0.379–0.573 μm to 0.291–0.368 μm, which fully met the processing requirement of Ra <0.4 μm.